Bibliometric analysis on the use of ultrasound in oil type emulsions in oil (O / A) (Research, Society and Development, 2019)
A process that has been able to generate descaling of emulsions, removing a significant fraction of oil and other contaminants, is the ultrasound. The main advantages of applying an ultrasonic technique for the destabilization of emulsions are the efficiency, the non-use of chemical agents and the suitability of the technique to different emulsions. Therefore, this work proposes a bibliometry on the studies of ultrasonic probes and the assisted ultrasonic bath in oil-in-water (O / W) emulsions. Demonstrating the experiences of destabilizing the emulsions through the application of ultrasound. In this way, the papers were published about the country and the periodicals, year of publication and topics, showing a real lack of studies on the subject in recent years, being an opportunity to look at the use of ultrasound used in emulsions.